Prognostic value of CA 19-9, CEA, CRP, LDH and bilirubin levels in locally advanced and metastatic pancreatic cancer: results from a multicenter, pooled analysis of patients receiving palliative chemotherapy - Haas, Michael; Klose, Christina (Journal of cancer research and clinical oncology, 2013)
CA 19-9 is the only established tumor marker in pancreatic cancer (PC); the prognostic role of other serum markers like CEA, CRP, LDH or bilirubin has not yet been defined.
Gesehen am 10.02.2021